INVESTIGATING THE INFLUENCE OF PERSONAL SKILLS ON STUDENTS’ LEADERSHIP DEVELOPMENT IN HIGHER EDUCATION - Zulkifli Mohamed; Mohd Nasir Ismail; Khalid Abdul Wahid (Journal of Islamic, Social, Economics and Development, 2024)
This quantitative research study had investigated the influence of personal skills on the development of students' leadership models in higher education. The study specifically focused on personal skills such as self-enhancement, presentation skills and self-confidence, adopting technology, decision making and problem solving, responsibility and commitment, time management, communication and collaboration, and motivating and inspiring others. The sample are undergraduate students from various disciplines in Universiti Teknologi MARA, through a purposive sampling technique. The data were collected through a structured questionnaire designed to measure the students' self-reported levels of personal skills and their perceived impact on leadership development. The research objectives included: (1) assessing the levels of personal skills, (2) examining the relationship between personal skills and the development of students' leadership models, and (3) identifying the most influential personal skills in shaping students' leadership models. The data analysis were involved a descriptive statistics to determine the distribution of personal skills among the participants, as well as inferential statistics to explore the relationships between personal skills and leadership development. This study had contributed to the existing literature on leadership development in higher education by highlighting the significance of personal skills in shaping students' leadership models. The findings had provided valuable insights for educational institutions, curriculum designers, and student development practitioners to enhance leadership education programs and foster the cultivation of effective leadership skills among students